Linkage between Dizziness and Balance in Vertigo - S. D. Shahanawaz (Current Overview on Disease and Health Research Vol. 1, 2022)
The vestibular system has both a sensory and a motor component. The vestibular system, as a sensory system, informs the central nervous system (CNS) about the location and motion of the head, as well as the direction of gravity. This information, along with information from other sensory systems, is used by the CNS. Tilts in relation to gravity and slow, drifting movements can be detected by the otolith organs, but only when the movements are linear rather than rotational. The study’s goal was to look into the relationship between dizziness and balance in BPPV patients using the outcome measures Dizziness Handicap Inventory and Berg Balance Scale. A total of 56 people were enrolled in the study. Males and females between the ages of 18 and 65. Ability to experience symptoms for a three-month period; ability to shift from sitting to standing and walk independently. We were able to tolerate the exercise and conducted a descriptive, analytical, and correlational investigation. We took data from patients who were treated for 9 weeks with an exercise protocol and an outcome measure of dizzy handicap inventory and berg balance scale from this study. Validity was tested by assessing the degree to which DHI total score and DHI sub scale components i.e physical, functional, emotional correlated with the Berg balance scale, by Spearman correlation coefficient.The study found that the higher the improvement in dizziness, the better the balance of dizziness induced by BPPV, and that there is a stronger functional component of co-relationship.